Numerical analysis of slab effects in reinforced-concrete frames to resist progressive collapse - Arroyo Jhunel Arian Sadural (2014)
Research interest in the topic of progressive collapse, has heightened in the recent decade due to its catastrophic consequences. Progressive collapse, which is defined as the widespread propagation of an initial local failure to a disproportionately large scale, can be caused by terrorist attacks or other blast loadings targeted to a structure’s columns. However, most of the previous researches have only studied the secondary load-carrying mechanisms in two-dimensional (2D) planar frames and neglected additional load-carrying capacity provided by three-dimensional (3D) effects and slab effects. This project aimed to study the effectiveness of finite-element models in quantifying the additional load-carrying capacity of three-dimensional effects and slab effects in resisting progressive collapse. A parametric study was also done to study the critical parameters that affect the structure’s resistance. Finite-element models were produced corresponding to the specimens used in Qian et al.’s (2013) experimental study on 3D and slab effects and were simulated under a quasi-static interior column removal scenario. These models were also modified to study the effects of the frame specimens’ boundary condition, reinforcement ratios, beam span-depth ratio, and slab span-thickness ratio in the load-displacement response of the said frame specimen. Results from the finite-element models predicted the load-displacement response of the specimens with reasonable accuracy having shown good agreement with the experimental results from Qian et al. The parametric studies have also shown that the equivalent-fixed boundary conditions on the columns assumed by Qian et al are reasonably acceptable with comparison to the realistic boundary conditions. Lastly, it was shown that increasing the beam and slab’s reinforcement ratio generally increases progressive collapse performance while, increasing the beam span-depth ratio and slab span-thickness ratio decreases the initial peak strength of the specimens. It was then concluded that the finite-element modeling is a useful and accurate tool in studying the contribution of slab effects in resisting progressive collapse. However, it is recommended to use more realistic boundary conditions in the specimens in future experiments to improve the accuracy of results.